GROUTING AS A MEAN FOR REPAIRING EARTH CONSTRUCTIONS - Silva, Rui; Schueremans, Luc; Oliveira, Daniel (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2010)
A good condition of the structural elements of an earth construction is essential for a good global structural behaviour. Therefore, the absence of major cracks is essential. Repairing cracks by using traditional techniques, involving the partial or the total reconstructions of the structural elements, constitutes a very intrusive solution that must, necessarily, be avoided in the case of historical earth constructions. Grouting constitutes an alternative and more practical solution for solving this problem. However, the design of the grouts for earth constructions demands the implementation of a methodical process that accounts both for the structural and durability demands of the construction. Previous works showed that the injection of mud grouts is a reliable and feasible solution. However, the knowledge developed is still very limited, hindering the further development of a methodology for designing mud grouts for earth constructions. Therefore, in this paper an initial methodology proposal for the design of mud grouts is presented and discussed. This results from an ongoing research that aims at the development of suitable grouts for earth constructions.